A compression-resistant concrete containing solid waste and a process for preparing the same
Patent Information
- Application Number
- CN202410747311.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-06-11
AI Technical Summary
[0004]本发明提出一种含固体废弃物的抗压混凝土及其制备工艺,解决了相关技术中的粉煤灰制备的混凝土抗压强度低的问题
本发明中经聚丙烯酰胺和聚二硫二丙烷磺酸钠改性的粉煤灰提高了混凝土的抗压强度和抗折强度。原因在于:粉煤灰经改性后表面包覆有聚丙烯酰胺和聚二硫二丙烷磺酸钠,其中聚丙烯酰胺中含有亲水性的酰胺基,在水介质中,可以形成氢键等吸附单元,还可以形成以水化膜为主的空间网络,从而使粉煤灰在短时间内产生粘稠性水化膜,使粉煤灰短时间内“活化”和“水化”;同时聚二硫二丙烷磺酸钠可以使粉煤灰表面带有相同电荷,提高了粉煤灰的分散性,此外聚二硫二丙烷磺酸钠还可以提供钠离子作为混凝土碳化的催化剂,促进碳化反应的进行生成碳酸钙,提高混凝土整体的密实度,达到了提高混凝土的抗压强度和抗折强度的效果。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete technology, specifically to a compressive-resistant concrete containing solid waste and its preparation process. Background Technology
[0002] With rapid societal development and accelerated urbanization, the amount of solid waste generated is increasing daily. Utilizing solid waste to produce concrete can not only effectively treat solid waste but also reduce production costs, thus providing a low-cost, sustainable building material.
[0003] Solid waste can be classified into three types according to particle size: block, granular, and powder. Fly ash, as a representative of powdery solid waste, is widely used in concrete, but the compressive strength of the concrete prepared by it needs to be further improved. Summary of the Invention
[0004] This invention proposes a compressive strength concrete containing solid waste and its preparation process, which solves the problem of low compressive strength of concrete prepared from fly ash in related technologies.
[0005] The technical solution of the present invention is as follows: A type of compressive concrete containing solid waste comprises the following components in parts by weight: 25-30 parts cement, 75-80 parts crushed stone, 72-78 parts sand, 15-25 parts modified fly ash, 5-10 parts mineral powder, 2-5 parts fiber, 0.5-1 part water-reducing agent, and 15-20 parts water. The modified fly ash is fly ash modified with polyacrylamide and sodium polydisulfide dipropane sulfonate.
[0006] As a further technical solution, the water-reducing agent includes one or two of polycarboxylate water-reducing agents and naphthalene-based water-reducing agents.
[0007] As a further technical solution, in the modified fly ash, the mass ratio of fly ash, polyacrylamide, and sodium polydisulfide dipropane sulfonate is 25:1.5:3~5.
[0008] This invention limits the mass ratio of fly ash, polyacrylamide, and sodium polydisulfide dipropane sulfonate to 25:1.5:3~5, which further improves the compressive strength and flexural strength of concrete.
[0009] As a further technical solution, the preparation method of the modified fly ash includes the following steps: mixing sodium polydisulfide dipropane sulfonate, polyacrylamide and water, adding fly ash and continuing to mix evenly, filtering, and drying to obtain modified fly ash.
[0010] As a further technical solution, the fiber is a modified fiber, which is a fiber modified with polyacrylonitrile and carbon nanotubes.
[0011] This invention utilizes fibers modified with polyacrylonitrile and carbon nanotubes, which, when combined with modified fly ash, improve the compressive and flexural strength of concrete. The modification of the fibers with polyacrylonitrile and carbon nanotubes results in a rougher surface, increasing friction and thus enhancing the filling and compacting effect with the modified fly ash.
[0012] As a further technical solution, in the modified fiber, the mass ratio of fiber, polyacrylonitrile and carbon nanotubes is 5:0.8:0.5~1.5.
[0013] As a further technical solution, the mass ratio of fiber, polyacrylonitrile, and carbon nanotubes in the modified fiber is 5:0.8:1.
[0014] This invention limits the mass ratio of fiber, polyacrylonitrile, and carbon nanotubes to 5:0.8:1, which further improves the compressive and flexural strength of concrete.
[0015] As a further technical solution, the preparation method of the modified fiber includes the following steps: dissolving polyacrylonitrile in a solvent, then adding carbon nanotubes and fibers in sequence, mixing evenly, filtering, and drying to obtain the modified fiber.
[0016] As a further technical solution, the fiber includes one or both of carbon fiber and glass fiber.
[0017] As a further technical solution, the carbon nanotubes include one or both of single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0018] As a further technical solution, the mass ratio of the modified fly ash to the modified fiber is 5:0.7.
[0019] This invention limits the mass ratio of modified fly ash to modified fiber to 5:0.7, which further improves the compressive strength and flexural strength of concrete.
[0020] The present invention also proposes a preparation process for compressive concrete containing solid waste, wherein the components of the stated mass fraction are mixed uniformly to obtain compressive concrete.
[0021] The working principle and beneficial effects of this invention are as follows: In this invention, fly ash modified with polyacrylamide and sodium didithiopropane sulfonate improves the compressive and flexural strength of concrete. The reason is that after modification, the fly ash surface is coated with polyacrylamide and sodium didithiopropane sulfonate. Polyacrylamide contains hydrophilic amide groups, which can form adsorption units such as hydrogen bonds in an aqueous medium, and can also form a spatial network mainly composed of a hydration film. This allows the fly ash to form a viscous hydration film in a short time, enabling the fly ash to be "activated" and "hydrated" quickly. Simultaneously, sodium didithiopropane sulfonate can impart the same charge to the fly ash surface, improving its dispersibility. Furthermore, sodium didithiopropane sulfonate can provide sodium ions as a catalyst for concrete carbonation, promoting the carbonation reaction to generate calcium carbonate, increasing the overall density of the concrete, and thus improving the compressive and flexural strength of the concrete. Detailed Implementation
[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0023] In the following embodiments and comparative examples: The cement is ordinary Portland cement P.O42.5; The crushed stone is from a construction factory. Before use, flaky and needle-shaped stones are removed by screening. The crushed stone gradation conforms to a continuous gradation of 0.5~2.5cm. The sand is river sand with a fineness modulus of 2.2; The fly ash is Grade I fly ash with a particle size of 400 mesh. Its composition includes: SiO2: 34.30wt%~65.76wt%, Al2O3: 14.59wt%~40.12wt%, Fe2O3: 1.50wt%~6.22wt%, CaO: 0.44wt%~16.80wt%, MgO: 0.20wt%~3.72wt%, SO3: 0.00wt%~6.00wt%, Na2O: 0.10wt%~4.23wt%, K2O: 0.02wt%~2.14wt%, and loss on ignition: 0.63wt%~29.97wt%. The mineral powder is S95 grade mineral powder; The polyacrylamide is a nonionic polyacrylamide with a weight-average molecular weight of 3 million and an effective substance content of 98 wt%. Polyacrylonitrile is industrial grade with a weight-average molecular weight of 140,000. Both carbon fiber and glass fiber are 12mm in length; Single-walled carbon nanotubes have a diameter of 1-2 nm, a length of 5-30 μm, a purity of >95%, and a specific surface area of >450 m². 2 / g, bulk density 0.14g / cm³ 3 ; The polycarboxylate superplasticizer is Sika superplasticizer 530P; The naphthalene-based water-reducing agent is Point-N200, a high-efficiency naphthalene-based water-reducing agent.
[0024] Example 1 S1. Dissolve 1g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 2 parts carbon fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0025] Example 2 S1. Dissolve 1g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Mix 25 parts cement, 75 parts crushed stone, 72 parts sand, 15 parts modified fly ash, 5 parts mineral powder, 2 parts glass fiber, 0.5 parts naphthalene-based water-reducing agent, and 15 parts water evenly to obtain concrete.
[0026] Example 3 S1. Dissolve 3g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 2 parts carbon fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0027] Example 4 S1. Dissolve 5g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 2 parts carbon fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0028] Example 5 S1. Dissolve 7g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 2 parts carbon fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0029] Example 6 S1. Dissolve 5g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Dissolve 0.8g of polyacrylonitrile in 80mL of N,N-dimethylformamide, add 0.5g of single-walled carbon nanotubes and stir at 400rpm for 10min. After sonicating at 600W for 15min, add 5g of carbon fiber and continue stirring at 400rpm for 20min. Filter, wash with water, and dry to obtain modified fiber. S3. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 2 parts modified fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0030] Example 7 S1. Dissolve 5g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Dissolve 0.8g of polyacrylonitrile in 80mL of N,N-dimethylformamide, add 1g of single-walled carbon nanotubes and stir at 400rpm for 10min. After sonicating at 600W for 15min, add 5g of carbon fiber and continue stirring at 400rpm for 20min. Filter, wash with water, and dry to obtain modified fiber. S3. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 2 parts modified fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0031] Example 8 S1. Dissolve 5g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Dissolve 0.8g of polyacrylonitrile in 80mL of N,N-dimethylformamide, add 1.5g of single-walled carbon nanotubes and stir at 400rpm for 10min. After sonicating at 600W for 15min, add 5g of carbon fiber and continue stirring at 400rpm for 20min. Filter, wash with water, and dry to obtain modified fiber. S3. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 2 parts modified fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0032] Example 9 S1. Dissolve 5g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Dissolve 0.8g of polyacrylonitrile in 80mL of N,N-dimethylformamide, add 1g of single-walled carbon nanotubes and stir at 400rpm for 10min. After sonicating at 600W for 15min, add 5g of carbon fiber and continue stirring at 400rpm for 20min. Filter, wash with water, and dry to obtain modified fiber. S3. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 3.5 parts modified fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0033] Example 10 S1. Dissolve 5g of sodium polydisulfide dipropane sulfonate in 300mL of water, add 1.5g of polyacrylamide and stir at 400rpm for 20min until dissolved, add 25g of fly ash and continue stirring for 30min, then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Dissolve 0.8g of polyacrylonitrile in 80mL of N,N-dimethylformamide, add 1g of single-walled carbon nanotubes and stir at 400rpm for 10min. After sonicating at 600W for 15min, add 5g of carbon fiber and continue stirring at 400rpm for 20min. Filter, wash with water, and dry to obtain modified fiber. S3. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 5 parts modified fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0034] Comparative Example 1 Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts fly ash, 10 parts mineral powder, 2 parts carbon fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0035] Comparative Example 2 S1. Add 1.5g of polyacrylamide to 300mL of water and stir at 400rpm for 20min until dissolved. Add 25g of fly ash and continue stirring for 30min. Then sonicate at 600W for 10min, filter, and dry to obtain modified fly ash. S2. Mix 30 parts cement, 80 parts crushed stone, 78 parts sand, 25 parts modified fly ash, 10 parts mineral powder, 2 parts carbon fiber, 1 part polycarboxylate superplasticizer, and 20 parts water evenly to obtain concrete.
[0036] The concrete obtained from Examples 1-10 and Comparative Examples 1-2 were cured in a standard curing room according to GB / T 50081-2019. After preparing standard specimens, the 28-day compressive strength and 28-day flexural strength were tested respectively, and the test results are recorded in Table 1.
[0037] Table 1 Compressive and flexural strengths of concrete
[0038] As can be seen from Table 1, the concrete provided by the present invention has a 28-day compressive strength of over 58.9 MPa and a 28-day flexural strength of over 7.9 MPa, exhibiting high compressive and flexural strength.
[0039] Compared with Comparative Examples 1 and 2, Examples 1 to 10 used fly ash modified with polyacrylamide and sodium polydisulfide sulfonate, while Comparative Example 1 used unmodified fly ash and Comparative Example 2 used fly ash modified with polyacrylamide. The 28-day compressive strength and 28-day flexural strength of the concrete obtained in Examples 1 to 10 were higher than those in Comparative Examples 1 and 2, indicating that using fly ash modified with polyacrylamide and sodium polydisulfide sulfonate can improve the compressive strength and flexural strength of concrete.
[0040] The 28-day compressive strength and 28-day flexural strength of the concrete obtained in Examples 6-10 were higher than those in Examples 1-5, indicating that the addition of fibers modified with polyacrylonitrile and carbon nanotubes can further improve the compressive strength and flexural strength of concrete.
[0041] The concrete obtained in Example 9 had better 28-day compressive strength and 28-day flexural strength than the other examples, indicating that the mass ratio of modified fly ash to modified fiber of 5:0.7 can further improve the compressive strength and flexural strength of concrete.
[0042] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A type of compressive concrete containing solid waste, characterized in that, The components include the following parts by weight: 25-30 parts cement, 75-80 parts crushed stone, 72-78 parts sand, 15-25 parts modified fly ash, 5-10 parts mineral powder, 2-5 parts fiber, 0.5-1 part water-reducing agent, and 15-20 parts water. The modified fly ash is fly ash modified with polyacrylamide and sodium polydisulfide dipropane sulfonate; the fiber is a modified fiber, specifically a fiber modified with polyacrylonitrile and carbon nanotubes. In the modified fiber, the mass ratio of fiber, polyacrylonitrile, and carbon nanotube is 5:0.8:0.5~1.5; the preparation method of the modified fiber includes the following steps: dissolving polyacrylonitrile in a solvent, then adding carbon nanotube and fiber in sequence, mixing evenly, filtering, and drying to obtain the modified fiber; In the modified fly ash, the mass ratio of fly ash, polyacrylamide, and sodium polydisulfide dipropane sulfonate is 25:1.5:3~5. The method for preparing the modified fly ash includes the following steps: mixing sodium polydisulfide dipropane sulfonate, polyacrylamide and water, adding fly ash and mixing evenly, filtering, and drying to obtain modified fly ash.
2. The compressive concrete containing solid waste according to claim 1, characterized in that, The fiber includes one or both of carbon fiber and glass fiber.
3. The compressive concrete containing solid waste according to claim 1, characterized in that, The carbon nanotubes include one or both of single-walled carbon nanotubes and multi-walled carbon nanotubes.
4. The compressive concrete containing solid waste according to claim 1, characterized in that, The mass ratio of the modified fly ash to the modified fiber is 5:0.
7.
5. The preparation process of a compressive concrete containing solid waste according to any one of claims 1 to 4, characterized in that, The components by mass are mixed evenly to obtain compressive concrete.
Citation Information
Patent Citations
Grinding aid material for improving fluidity of fly ash, and use method thereof
CN109111150A
Compressive concrete and preparation method thereof
CN111205034A